Corporate Purpose Needs Democracy. (4th December 2020) - Davis, Gerald F.
Abstract: The British Academy proposes that some of the manifest failures of shareholder capitalism can be addressed by requiring corporations to declare a purpose – a profitable solution to the problems of people and planet that does not cause additional problems – and creating a set of supporting mechanisms to ensure the pursuit of purpose. Shareholder capitalism has a lot to answer for, arguably including the opioid and obesity epidemics, the hazards to people and democracy posed by profit‐driven tech firms, and catastrophic climate change. Moreover, the forces that orient public corporations toward share price are powerful and pervasive, while public corporations are disappearing in the USA and the UK under the weight of outside pressures. If we want the corporations that remain to behave themselves, the surest path is more democracy: greater worker control from below, and more effective state regulation from above.